PRINCIPLES AND PRACTICE OF DIGITAL ARBITRATION (Academicia Globe: Inderscience Research, 2022)
E-arbitration is a key component of online dispute resolution (ODR, which allows parties to resolve any issue originating from their contractual relationship online. E-arbitration is primarily used to resolve Business to Business (B2B) cross-border e-commerce conflicts, but it is also used to resolve traditional cross-border commercial disputes. The arbitration agreement and the arbitral process are both completed online in e-arbitration. Some analysts argue that the form requirement in e-commerce contracts, including arbitration agreements, is less necessary if the electronic document is sufficiently specific, establishing obvious indicators that can be read in the future.